Loading effect of a barium titanate artificial interface on high voltage capabilities at high charge and discharge rates. (5th September 2017) - Yoshikawa, Yumi; Teranishi, Takashi; Hayashi, Hidetaka; Kishimoto, Akira
Abstract: Cyclic characteristics of BaTiO3 (BT)-decorated LiCoO2 (LC), for use as an artificial solid electrolyte interface (SEI) were evaluated at high voltages. Within the standard voltage window (i.e., 3.3–4.2 V), the BT-decorated LC exhibited greater capacities for up to 80 cycles compared with both the Al2 O3 (paraelectric)-decorated and bare LC SEIs. The discharge capacity retention after 80 cycles (compared with the initial value) was 86.0% for the BT–LC cathode. This is a significant improvement over both the bare LC that showed 19.9% retention and the Al2 O3 –LC that displayed 71.5% retention. Thereafter, the cyclic stabilities of the BT–LC and bare LC were compared within potential windows at cutoff voltages as high as 4.9 V. In this region, BT decoration yielded marked improvements in capacity retention after 50 cycles, up to a potential of 4.7 V. The post-situ XRD analysis of the cathode sheets showed that BT decoration effectively stabilized the hexagonal crystal structure of the LC, H1, resulting in the said cyclic stability increase. These observations demonstrate that the use of BT in SEI allows a significant increase in working voltage while maintaining the chemical stability of the underlying LC matrix, a key advancement in the perpetual pursuit of ever higher cell energy densities.